Украинская социология после 1991 года - Резник, А.; Резник, В. (Социология: теория, методы, маркетинг, 2004)
The article is about specific features of institutional ground development of Ukrainian sociology from 1990 to the beginning of 2004. Basing on empirical data related to distribution of Candidate and Doctor dissertations, authors determine the main tendencies in growth of the scientific and professional sociological community. There are discussed the current state and prospects of research by Ukrainian sociologists, analyzed relations between sociology and a transforming society.